2019
DOI: 10.1049/mnl.2019.0033
|View full text |Cite
|
Sign up to set email alerts
|

Role of a nanoparticle on ultrasonic cavitation in nanofluids

Abstract: Ultrasonic cavitation in nanofluids improves material removal rate and surface quality. Ultrasonic cavitation in nanofluids was investigated using molecular dynamics simulations. The formation and growth of nanobubbles were promoted, by nanoparticles in water systems. Three distinct impact stages were observed which were caused by the impact of the shock wave, nanojet and nanoparticle. These differed in the system without a nanoparticle. The material removal rate was primarily caused by the nanoparticle hit, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The generally accepted shock wave and micro-jet generation process [29] is that the shock wave generated by the cavitation cloud contacts the cavitation bubble near the wall, resulting in different pressures up to and below the spherical cavitation bubble; the bubble collapses and releases energy to generate micro-jets. Concurrently, generated shock waves and micro-jets [30] are the sources of micro-abrasive acceleration. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The generally accepted shock wave and micro-jet generation process [29] is that the shock wave generated by the cavitation cloud contacts the cavitation bubble near the wall, resulting in different pressures up to and below the spherical cavitation bubble; the bubble collapses and releases energy to generate micro-jets. Concurrently, generated shock waves and micro-jets [30] are the sources of micro-abrasive acceleration. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…If the amplitude of the alternating sound pressure exceeds a certain value (cavitation threshold), the nuclei of cavitation forms, grows, and ultimately cracks within the liquid or at the liquid–solid interface. Studies have shown that the crack of cavitation bubbles generates elevated temperatures, pressures, microjets [52] , [53] , [54] , [55] , [56] , [57] . In a review article on acoustic cavitation published in 1980, Neppiras used the term “ultrasonic cavitation” as an academic term.…”
Section: Ultrasoundmentioning
confidence: 99%
“…After the ultrasonic wave propagates in the water, the underwater ultrasonic field is formed. When there are particles in the ultrasonic field, the particles will be affected by the inherent properties of the ultrasonic field [1,2], such as the cavitation and mechanical action of ultrasound [3,4]. Studying the characteristics of particles in the ultrasonic field and making use of them makes ultrasonic applications in many important technologies, such as ultrasonic cleaning [5], ultrasonic atomization and applications in sewage treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%